Morphogenesis of Stamens and Petaloid Stamens in Lilium hybrid ‘Red Twin’ under Different Temperatures and the Expression Characteristics of Two AGAMOUS-like Genes Linked to These Processes - Xin Li; Zhen Wang; Minmin Chen; Liuyan Yang; Yongchun Zhang (Horticulturae, 2022)
The double-flowered lily ‘Red Twin’, in which stamens are transformed into petaloid organs, sometimes exhibits normal stamens owing to an unknown mechanism and thus greatly affecting its commercial quality. In this study, the morphogenesis of stamens and petaloid stamens in this cultivar grown under different temperature treatments were investigated. Two AGAMOUS-like genes were isolated and their expression levels were analyzed. The results showed that relatively high temperatures induced the morphogenesis of stamens, while relatively low temperatures promoted petaloidy in ‘Red Twin’. The stage with 1–6 mm flower buds was identified as the critical development period for stamen morphogenesis; furthermore, keeping the flower buds under relatively low temperatures in the 1–3 or 3–6 mm stages would be sufficient for the formation of petaloid stamens to a high degree. In addition, LrtAG1 and LrtAG2 showed the highest expression level in whorls 3 and 4 of 3–6 mm flower buds, respectively. LrtAG1 showed a higher reduction ratio than LrtAG2 when the flower buds were transferred to low temperature, implying that the decreased LrtAG1 expression level is associated with low temperature and might be correlated with the petaloidy of the stamens.